Study of Ordering in Fe—25%Al—Cr Alloys by Dilatometry, Heat Flow and Mechanical Spectroscopy - Belamri, Z.; Hamana, D.; Golovin, I.S.; Chudakov, I.B. (Металлофизика и новейшие технологии, 2013)
It is known that the addition of Cr to the Fe₃Al-based alloys leads to an improvement in their ductility and other properties. In a given work, dilatometric, differential scanning calorimetric (DSC) and internal friction tests are performed to study the ordering process in stoichiometric and overstoichiometric Fe₃Al alloys with Cr addition at a constant heating rate from room temperature up to 1000°C. The results indicate that the addition of Cr slows the D0₃-type ordering process; this can be confirmed by obtained values of activation energy. Cr addition has also an effect on the mechanical properties of studied alloys annealed in D0₃-type order domain. The heights and broadening of three peaks (of X-, Zener-, and Snoek-type) can be changed at the presence of Cr. X-ray diffraction (XRD) and TEM studies are carried out at different temperatures chosen from the obtained DSC curves and affirmed that a rapid quenching just after heat treatment from highest temperature cannot suppress the formation of B2 ordered particles in overstoichiometric Fe₃Al alloys.